Does Gen-Z have a higher organizational culture and organizational commitment to work performance than other generations - Putri, Kenita (Institute of Computer Science (IOCS), 2024)
The aim of this research is to determine the influence of organizational culture and organizational commitment on work performance by comparing three generations X, Y and Z. The population in this study are employees in the Cikarang area with age categories corresponding to generations Respondents were involved in this research and were selected using stratified random sampling techniques. The statistical test technique used is the Normality test and homogeneity test. The hypothesis testing technique used is two-way Anova. The research results show that there are significant differences in generational differences, where Gen-Z has a higher organizational culture and organizational commitment than generations X and Y and this is a factor that can influence achievement. Implications and suggestions are explained in the article